Editorial Preface - Daud, Zawawi; Ismail, Al Emran; Ibrahim, Nabilah (International Journal of Integrated Engineering, 2017)
It is with great pleasure that we present the 3rd issue of Volume 9 of the International Journal of Integrated Engineering (IJIE). This edition features the latest findings and research in the area of Civil and Environmental Engineering, Electrical and Electronic Engineering and Mechanical, Materials and Manufacturing Engineering.This issue contains eleven articles. The first article proposed a new solution, named RRFAST, to overcome rerouting problem of FAST TCP. The second article aimed to study and assess the diameter and displacement of the carotid arterial wall movement from B-mode ultrasound image for the early detection of atherosclerosis. The third article presented a Multi-Criteria Decision Making (MCDM) tool for prioritising alternative solutions to power generation problems. The fourth article focused on determining the characteristics of the spray produced in the simulation of spray biodiesel using constant volume chamber by using computational fluid dynamic (CFD). The fifth article presents a development of a temperature control system by means of the proportional controller to control the temperature inside the mini container during the NIRS data acquisition process. In the sixth article, the authors developed a single phase inverter that is used to understand the concept of inverting voltage output control using Raspberry Pi as the microcontroller. In the seventh article, the authors present their finding on the capability of peat soil (PS) and activated carbon (AC) as a potential composite adsorbent for the removal of colour and Fe from a stabilized landfill leachate. The eighth article presents the design and development of a simple and low cost interactive rehabilitation module for stroke patients. In the ninth article, the authors share their findings on the combination of Charge-Coupled Device (CCD) and laser diode with LabVIEW software on Optical Tomography System (OTS) for monitoring multiphase flow. In the tenth article, the authors examined the effect of different spatial filters performance towards mammogram de-noising. In the last article, the authors report on the efficiency of coagulation and flocculation process in the removal of suspended solids, colour, Chemical Oxygen Demand (COD) and Oil and Grease using ferric chloride and ferric sulfate for the treatment of biodiesel wastewater.We would like to extend our sincere gratitude and appreciation for the enthusiastic and vigorous support and contributions from the Editorial Board and Reviewers of IJIE for taking time and effort to review manuscripts. As no manuscript is accepted or rejected without careful reading by experts in a particular area to which the paper is related. The experts have maintained a high standard of scholarship and we believe the readers of this Journal deserves.It is our hope that this fine collection of articles will be a valuable resource for International Journal of Integrated Engineering (IJIE) readers and will stimulate further research in the area of Civil and Environmental Engineering, Electrical and Electronic Engineering and Mechanical, Materials and Manufacturing Engineering. We strongly encourage authors to submit their articles and readers to provide feedback. In order to access the online version of this issue along with archived editions please visit our website http://penerbit.uthm.edu.my/ojs/index.php/ijie/. We would like to thank all the authors who have contributed manuscripts in IJIE and those who are awaiting their manuscripts for publication in subsequent issues.